Attentional control and biases towards threat : theoretical foundations and adaptation of experimental tasks - Silva, Gustavo Ramos (2018)
Attention is a multifaceted construct, one that has been at the center of discussions across several moments in the history of philosophy and psychology. The characteristic of attention to influence and regulate many other psychological process (e.g., consciousness, memory, decision-making) stresses its importance, and logically results in a hardship in segregating its theoretical boundaries and clearly defining this phenomenon. In a current empirical field of research on attention, biases of attentional orientation to threatening stimuli are investigated. However, models generated from empirical findings lack sustentation on well-established theoretical models of attention, and confusion exists across published experimental studies. Furthermore, experimental tasks to assess biases towards threat require integration with new operationalization and analysis strategies, which can provide better sensitivity, validity and measurement reliability, such as eye tracking and the novel index of attentional bias variability (ABV). This dissertation is included in the subarea number 7.07.02.03-9 of the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) – Experimental Psychology (Attentional and Cognitive Processes) – which integrates the broader area of Psychology. Two studies are presented to answer to the need of advancing research about attention, attentional control (AC) and attentional bias relative to threat (ABT). Firstly, a theoretical study provides a historical overview of psychological research on attention, from the founders of modern Psychology to current neuropsychological integrative research and empirically-oriented models. This review is expected to clarify constructs of attention and to differentiate these constructs from those of other Psychological domains. Instead of segregating research fields, this is likely to promote a 9 dialogue between fields that research the same phenomena – but measure them differently and attribute to them different names. Following this theoretical review, an empirical study is presented, which proposes two adaptations of classical experimental tasks to measure ABT: the DotProbe Task (DPT) and the Emotional Stroop Task (EST). On the EST, task design is altered to account for important theoretical considerations and to better adapt the task to the measurement of ABV. On the DPT, a surprisingly rare integration of reaction times and eye tracking measures is established, and novel indices to calculate ABT and ABV are proposed. The reliability and validity of indices in both tasks is investigated with university students and through the differentiation of such indices between groups of high vs. low symptoms of anxiety and posttraumatic stress. The importance of pursuing the improvement of psychometric qualities of experimental tasks is discussed in depth upon the findings of the study, including recommendations to future experimental designs.